Hepatotoxicity and Mutagenicity assessment during chronic in vivo exposure to aqueous extracts from Peperomia pellucida - YU-WEN HUANG; ARIANNE JAN TUOZO; ROGER S. TAN (Anais da Academia Brasileira de Ciências, 2022)
Abstract Studies on herbal medicine have exposed some toxic effects on humans. Peperomia pellucida (L.) HBK (P. pellucida) is one of the herbal medicines recommended as an alternative to synthetic medicine for diseases. Studies exist on the pharmacological activities of P. pellucida extracts, but studies on the potential hepatotoxic and mutagenic effects of subchronic administration of P. pellucida aqueous extracts, which is very important knowledge when we venture into alternative medicine, are lacking. In this study, two concentrations (60 mg/kg and 30 mg/kg) of P. pellucida aqueous extracts — decoction and freeze-dried extracts —were administered in vivo to BALB/c mice for nine (9) weeks. Significant differences were observed between the 60 mg/kg freeze-dried extract and the control in terms of mice weight and micronucleus frequency at 7-8 weeks of treatment. Also, no significant differences were found between groups in serum transaminases levels. Generally, there is no sufficient evidence to show that subchronic exposure to P. pellucida aqueous extracts is hepatotoxic though 60 mg/kg concentration may be mutagenic. This study suggests that although the herbal medicine is safe for prolonged consumption, users are advised to take precautions and moderations of its use due to the possibility of potential mutagenic effects.